Residual strength analysis of pipeline with circumferential groove corrosion subjected to internal pressure. (2020) - Arumugam, Thibankumar; Karuppanan, Saravanan; Ovinis, Mark
Abstract: This paper describes the application of finite element method (FEM) to predict the failure pressure of pipe with circumferential groove corrosion subjected to internal pressure. The FEM incorporated material nonlinearity and employed true UTS to determine the failure point. Finite element analysis (FEA) results were used to determine the failure trends of circumferential groove corrosion. Since DNV-RP-F101 has limited parametric range for predicting the failure pressure of circumferential groove corrosion subjected to internal pressure, several equations were then developed by utilizing Buckingham's π theorem and nonlinear multivariate regression techniques. These equations provide failure pressure predictions with errors less than 5%.